1949
DOI: 10.3181/00379727-72-17347
|View full text |Cite
|
Sign up to set email alerts
|

Mucoproteins of Human Plasma. III. Electrophoretic Studies of Mucoproteins from Perchloric Acid Filtrates of Plasma.

Abstract: animals the full supplement a t a time most conducive to overcoming the acute phase of the deficiency.The present data indicate that vit. B12 is about equally effective by oral or injection administration in promoting growth of young rats on highly specialized depletion diets. The deficiency of vit. Bl2 induced in rats by these rather extreme dietary means does not, therefore, appear to evoke a failure in utilization of the vitamin, but rather a true deficiency and enhanced need for the vitamin itself.The foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
7
0

Year Published

1951
1951
1971
1971

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(9 citation statements)
references
References 0 publications
2
7
0
Order By: Relevance
“…In one instance (case of gout) the increase in serum hexosamine was found to be in the hexosamines contained in the alpha-globulin fractions. This is consistent with observations that the alphaglobulins (12) and hexosamine-rich alpha-globulin mucoproteins (13,14) increase in response to other acute injuries or diseases such as burns (12) and pneumonia (13,14).…”
Section: Discussionsupporting
confidence: 79%
“…In one instance (case of gout) the increase in serum hexosamine was found to be in the hexosamines contained in the alpha-globulin fractions. This is consistent with observations that the alphaglobulins (12) and hexosamine-rich alpha-globulin mucoproteins (13,14) increase in response to other acute injuries or diseases such as burns (12) and pneumonia (13,14).…”
Section: Discussionsupporting
confidence: 79%
“…is.d. Gradient 3 of RS-1 had a mobility consistent with isolated serum MP-2, which Mehl and coworkers reported as -2.4 to -2.8 x 1O5 (7). This gradient appeared unchanged in fraction RS-1B as gradient 1.…”
Section: Mp-mp-imentioning
confidence: 69%
“…Alpha-2 mucoproteins include at least three electrophoretically homogenous components, all with isoelectric points of 3.7 to 4.4 (7,17). Haptoglobulin has an electrophoretic mobility similar to the alpha-2 globulins and has been recovered from human serum and nephrotic urine (14).…”
Section: Discussionmentioning
confidence: 99%
“…The vitamin B12 of normal and CML serum moves with the a-globulins when serum is electrophoresed at pH 8.6 (1,8,9). The seromucoid, the fraction of serum containing glycoproteins which comprises about 1.5 per cent of the serum proteins (10), moves with the a-globulins when electrophoresed at pH 8.6 (11). Furthermore, it has been found that the seromucoid fraction isolated from CML serum is capable of binding amounts of added cobaltOO-labeled vitamin B12 (B,2*) sufficient to account for the increased binding capacity of the whole serum (12).…”
mentioning
confidence: 99%